The Mediating Roles of Core Self-Evaluation and Career Exploration in the Association Between Proactive Personality and Job Search Clarity - Zhu, Hongrui; Zhang, Hua; Tu, Aixian; Zhang, Siqi (Frontiers in Psychology, 2021)
In recent years, university students’ employment has become increasingly prominent problem worldwide. Improving students’ job search clarity is a great way to boost job-hunt success. Proactive personality may predict job search clarity through the mediating effect of core self-evaluation and career exploration. But few studies have explored this relationship and the mediating roles of core self-evaluation and career exploration.In order to identify the relationship between proactive personality and job search clarity, and the mediating roles of core self-evaluation and career exploration.A cross-sectional survey was conducted. 495 students majored in nursing completed the questionnaire, which consisted of Proactive Personality Scale, Core Self-Evaluation Scale, Career Exploration Survey and Job Search Clarity Scale. Correlation analyses and mediation analyses were conducted by SPSS 24.0 and AMOS 24.0.This study shows that students high in proactive personality scale are more likely to perform better in job search clarity. Core self-evaluation, career exploration had fully mediating effect on the relationship between proactive personality and job search clarity. Therefore, interventions concentrated on cultivating proactive personality, improving core self-evaluation and strengthening career exploration will be necessary to increase job search clarity.